CD4+Foxp3+ regulatory T cell expansion induced by antigen-driven interaction with intestinal epithelial cells independent of local dendritic cells. Issue 2 (2nd October 2008) - Westendorf, A M; Fleissner, D; Groebe, L; Jung, S; Gruber, A D; Hansen, W; Buer, J
Abstract : Background: Regulatory T cells (Tregs ) have potential anti-inflammatory effects and are likely to be important in the pathogenesis of chronic inflammatory bowel disease (IBD). However, the induction and expansion of Tregs at sites of mucosal inflammation are not yet fully understood and may involve antigen presentation by local dendritic cells (DCs) and/or intestinal epithelial cells (IECs). Methods: To determine the unique ways in which the gut induces or expands Tregs, a transgenic mouse model that is based on the specific expression of a model autoantigen (influenza haemagglutinin (HA)) in the intestinal epithelium (VILLIN-HA) was used. Gut-associated DCs and IECs isolated from these mice were phenotypically and functionally characterised for the potential to interact with HA-specific Tregs in vitro and in vivo. Results: Intestinal self-antigen expression leads to peripheral expansion of antigen-specific CD4 + Foxp3 + Tregs . Although gut-associated DCs can induce antigen-specific CD4 + Foxp3 + T cell proliferation, in vivo depletion of DCs did not preclude proliferation of these cells. Interestingly, antigen presentation by primary IECs is sufficient to expand antigen-specific CD4 + Foxp3 + Tregs efficiently. This is dependent on major histocompatibility complex class II, but, in contrast to DCs, is unlikely to require transforming growth factor β and retinoic acid. Conclusion: This study provides experimental evidence for a new concept in mucosal immunity: in contrast to current thinking, expansion of Tregs can be achieved independently of local DCs through antigen-specific IEC–T cell interactions.